2022
DOI: 10.3390/ma15082919
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mechanical Properties and Damage Mechanism of Carbon Fiber/Epoxy Composites under UV Aging

Abstract: The UV durability of carbon fiber composites has been a concern. In this work, UV irradiation on carbon fiber-reinforced polymer (CFRP) materials was performed using an artificial accelerated UV aging chamber to investigate the effect of UV exposure on carbon fiber composites. UV aging caused some of the macromolecular chains on the surface resin to break, resulting in the loss of small molecules and loss of mass. After 80 days of UV irradiation exposure, a significant decline in the macroscopic mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Then, in the DSC curve of the CF composite (Figure S4) two T g s appear distinctly, confirming that a secondary transition occurs. Glass transition values superior to the DGEBA based carbon fiber composites reported in the literature (63–120 °C) , and comparable to that of the composite developed in this work are specified for commercial laminates such as Solvay CYCOM 890 RTM Resin-Woven Carbon Fabric Composite: T g = 169–210 °C; Polynt 90 CF40-400g Carbon Fiber Epoxy Fleece: T g = 150–200 °C; Solvay CYCOM 934 Epoxy-Carbon Fiber Reinforced Laminate: T g = 160–194 °C; or Park Aerospace Nelcote E-746 Epoxy Prepreg, 3k 5HS Carbon Reinforced: T g = 180–230 °C.…”
Section: Resultssupporting
confidence: 70%
“…Then, in the DSC curve of the CF composite (Figure S4) two T g s appear distinctly, confirming that a secondary transition occurs. Glass transition values superior to the DGEBA based carbon fiber composites reported in the literature (63–120 °C) , and comparable to that of the composite developed in this work are specified for commercial laminates such as Solvay CYCOM 890 RTM Resin-Woven Carbon Fabric Composite: T g = 169–210 °C; Polynt 90 CF40-400g Carbon Fiber Epoxy Fleece: T g = 150–200 °C; Solvay CYCOM 934 Epoxy-Carbon Fiber Reinforced Laminate: T g = 160–194 °C; or Park Aerospace Nelcote E-746 Epoxy Prepreg, 3k 5HS Carbon Reinforced: T g = 180–230 °C.…”
Section: Resultssupporting
confidence: 70%
“…Similar effects were found for CFRP IM7/997 [ 59 ], GFRP based on epoxy and polyester matrices [ 60 , 61 ], CFRP AS4/8552 [ 62 ], and CFRP based on T700 fiber [ 63 ]. In all cases, a decrease in mechanical properties of PCM is accompanied by damage at the polymer-filler interface and microcracks.…”
Section: The Role Of the Main Factors On The Uneven Aging Of Pcmsupporting
confidence: 58%
“…If thermal and moisture exposure is accompanied by UV irradiation, its simultaneous or alternate exposure significantly increases the likelihood of microcrack formation. This regularity was confirmed in [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: The Role Of the Main Factors On The Uneven Aging Of Pcmmentioning
confidence: 54%
“…Exposure of CFRP in open climatic conditions according to the data of [20,21] showed that as a result of exposure to temperature, freezing-thawing processes, marine chlorides in the air, aging occurs, accompanied by a change in mechanical properties. According to Shi et al [22] CFRP aging grows under the influence of the ultraviolet component of solar radiation.…”
Section: Introductionmentioning
confidence: 99%